INOVASI PEMBELAJARAN PANCASILA BERBASIS DEEP LEARNING DI SMK NEGERI 1 BELINYU - Hijran, Muhamad; Zahri, Tsulis Amiruddin (Penerbit Lafadz Jaya, 2025)
This research aims to explore the innovation of teaching the Pancasila subject by integrating deep learning technology at SMK Negeri 1 Belinyu. The background of this study is based on the need for an adaptive and contextual learning approach to improve students' understanding and internalization of Pancasila values in the digital generation. The method used is qualitative descriptive with a case study approach. Data collection techniques include in-depth interviews with Pancasila teachers, observation of learning activities, and documentation of digital-based teaching devices. The results show that the application of deep learning in Pancasila learning can provide a more personalized, interactive, and reflective learning experience for students. This innovation not only increases students' active participation but also encourages a deeper understanding of Pancasila values. However, there are still some obstacles, one of which is the lack of adequate digital infrastructure. This research recommends the importance of digital pedagogical training for teachers and school policy support to optimize the integration of technology in Pancasila learning.